Adaptive responses of animals to climate change are most likely insufficient - Viktoriia Radchuk (Nature Portfolio, 2019)
It is unclear whether species’ responses to climate change tend to be adaptive or sufficient to keep up with climate change. Here, Radchuk et al. perform a meta-analysis showing that in birds phenology has advanced adaptively in some species, though not all the way to the new optima.